Wreck-It Ralph [videorecording (DVD)] - Moore, Rich 1963-; Moore, Rich 1963-; Reilly, John C., 1965-; Silverman, Sarah; Lynch, Jane, 1960-; Tudyk, Alan; Kaling, Mindy; O'Neill, Ed, 1946-; McBrayer, Jack, 1973- (Disney DVD., 2013)
For decades, Ralph has played the bad guy in his popular video game. In a bold move, he embarks on an action-packed adventure and sets out to prove to everyone that he is a true hero with a big heart. As he explores exciting new worlds, he teams up with some unlikely new friends including feisty misfit Vanellope von Schweetz. Then, when an evil army threatens their world, Ralph realizes he holds the fate of the entire arcade in his massive hands.